Teachers perception of principals' instructional leadership functions [electronic resource] - 510150 Josephine Ihekerenma Okpareke (2010)
Thesis (Sarjana Pendidikan (Pengurusan dan Pentadbiran)) - Universiti Teknologi Malaysia, 2010